PRODUCTIVITY OF Panicum maximum cv. Trichoglume GRASS FED WITH DIFFERENT DOSAGE OF FOLIAR FERTILIZER - Y. F., Simbolon; Kusumawati, N. N. C.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the productivity of benggala grass (Panicum maximum cv. Trichoglume ) which was given with different dosage of foliar fertilizer. This research was conducted in a green house, on Jalan Raya Sading No. 93 mengwi, Badung, starting from July to September 2022. The experimental design used in this study was a completely randomized design (CRD) with four treatments and seven replications. The four treatments dosage of foliar fertilizers were: 0 kg ha -1 (P0), 200 kg ha -1 (P1), 400 kg ha -1 (P2) and 600 kg ha -1 (P3). The variables observed in this research were growth variables, production variables, and growth characteristic variables. The results showed that the plants treated with dosage of 600 kg ha -1 (P3) of foliar fertilizer gave the best results on all variables, both growth, yield and growth characteristics. Based on the results of this study it can be concluded that the of Benggala grass ( Panicum maximum cv. Trichoglume) which was given foliar fertilizer with different dosage was able not yet to increase productivity and the foliar fertilizer treatment at dosage of 600 kg ha -1 (P3) shows the best tending results in increasing the productivity of Benggala grass ( Panicum maximum cv. Trichoglume).